Synergistic Antibacterial Activity of Curcuma domestica Val. Extract with Tetracycline Against Multidrug-resistant Acinetobacter baumannii - Nasution, Halimah Raina; Yuandani, Yuandani; Septama, Abdi Wira; Nugraha, Sony Eka; Sufitni, Sufitni; Khairunnisa, Nur Aini (Molekul, 2024)
Infections caused by multidrug-resistant (MDR) bacteria are on the rise globally. MDR is facilitated by overexpression of efflux pump and permeability changes of membrane. Acinetobacter baumannii is a pathogenic germ that causes a major problem in infection, also, there has been an increase in the incidence of resistance to various antibiotics. The present study highlights the synergistic of ethanolic extract of Curcuma domestica (EECD) rhizome with tetracycline against multidrug-resistant A. baumannii (MDR-Ab). Assessment of Minimum Inhibitory Concentration (MIC) was determined by microdilution using 96-well plates. The synergistic effect of EECD and tetracycline was determined by checkerboard method. The effect of EECD and tetracycline combination was investigated by bacteriolytic activity and inhibition of efflux pump by Ethidium Bromide (EtBr) accumulation assay. EECD presented the MIC value 250 µg/mL against MDR-Ab. Fractional Inhibitory Concentration Index (FICI) value of EECD and tetracycline combination was 0.4, which showed their synergistic effect. Additionally, the combination of EECD and tetracycline could inhibit the efflux pump in MDR-Ab. This combination can also compromise cell integrity by altering membrane permeability thus lysing the bacteria cells. According to these results, EECD and tetracycline combination has synergistic effects at some sites of action, and thus could be used as a breakthrough to overcome infection problems due to MDR-Ab. Keywords: Acinetobacter baumannii, antibacterial, Curcuma domestica, multidrug-resistant, tetracycline